MicroRNA‐based diagnostic and therapeutic applications in cancer medicine. (17th May 2021) - Sempere, Lorenzo F.; Azmi, Asfar S.; Moore, Anna
Abstract: It has been almost two decades since the first link between microRNAs and cancer was established. In the ensuing years, this abundant class of short noncoding regulatory RNAs has been studied in virtually all cancer types. This tremendously large body of research has generated innovative technological advances for detection of microRNAs in tissue and bodily fluids, identified the diagnostic, prognostic, and/or predictive value of individual microRNAs or microRNA signatures as potential biomarkers for patient management, shed light on regulatory mechanisms of RNA–RNA interactions that modulate gene expression, uncovered cell‐autonomous and cell‐to‐cell communication roles of specific microRNAs, and developed a battery of viral and nonviral delivery approaches for therapeutic intervention. Despite these intense and prolific research efforts in preclinical and clinical settings, there are a limited number of microRNA‐based applications that have been incorporated into clinical practice. We review recent literature and ongoing clinical trials that highlight most promising approaches and standing challenges to translate these findings into viable microRNA‐based clinical tools for cancer medicine. This article is categorized under: RNA in Disease and Development > RNA in Disease Abstract : microRNAs are short noncoding regulatory RNAs with important roles in cancer biology. microRNAs are informative biomarkers for early cancer detection and treatment decisions. microRNAs are being evaluated in clinical trials as new drugs for personalized cancer medicine.